Ten-year surveillance of invasive Streptococcus pneumoniae isolates in central Turkey prior to the introduction of a conjugate vaccine - Duygu Percin; Yasemin Ay Altintop; Bulent Sumerkan (Journal of Infection in Developing Countries)
Introduction: The aim of this study was to characterize the serotypes and antimicrobial susceptibility patterns of invasive Streptococcus pneumoniae isolates in central Turkey.